Finding shortest paths in a sequence of triangles in 3D by the method of orienting curves. (2nd January 2018) - An, P. T.
Abstract: We present an efficient algorithm for finding the shortest path joining two points in a sequence of triangles in three-dimensional space without planar unfolding. The concept of a funnel associated with a common edge along a sequence of triangles is introduced, that is similar to Lee and Preparata's one in a simple polygon. The sequence of funnels associated with all common edges of the sequence is constructed and then the shortest path is determined by cusps of these funnels. Such funnels are determined iteratively to their associated edges by the Method of Orienting Curves, which was introduced by Phu [Ein konstruktives Lösungsverfahren für das Problem des Inpolygons kleinsten Umfangs von J. Steiner. Optimization. 1987;18:349–359]. The method consists of the concepts of final curves and orienting curves (the special cases of straightest geodesics). We then show that the shortest path from the cusp of a given funnel to the direct destination in the processed region of the funnel is determined by parts of orienting curves and a final curve. A numerical example for finding the shortest path joining two points in the sequence of triangles is presented and visualized by JavaView software.